Modeling the motion of a volleyball with spin - Ricardo, J. (Journal of the Advanced Undergraduate Physics Laboratory Investigation, 2014)
Though a qualitative understanding of how spin affects a ball`s trajectory can be easily developed, a quantitative one is relatively difficult to hone. Additionally, although projectile motion is an extensively covered topic in introductory physics courses, friction and drag—let alone spin—receive little to no attention. Here we use a volleyball and video modeling software to compare the behavior of a non-spinning ball with one that has topspin in order to assess the accuracy of our various models incorporating drag and the Magnus effect